PENGARUH PERMAINAN CROSSWORD PUZZLE TERHADAP MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK SD IT HARAPAN UMAT PURBALINGGA - Tri Rokhayati; Tukiran Tanuredja; Akhmad Jazuli (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2020)
This research purpose to knowing affected of: 1) crosswords puzzle learning to learn motivation at third class in Harapan Umat Elementary School IT Purbalingga, 2) crosswords puzzle learning to learn result in third class. The research method was an experiment, with two group treatments that were the control group and experiment group. Group control was 3C class and the experiment group was 3F class. Data using in this research were primary and secondary data. And then data be analyzed by the Independent Sample t-test. Result of the research has shown: 1) crosswords puzzle learning significant affected to learning motivation at third class in Harapan Umat Elementary School IT Purbalingga; and 2) crosswords puzzle learning affected to learning result at third class